Modeling interaction of pyridine on Mo2CuS8 for the HDN reaction. A theoretical study - Munaretto, Aldo; Ruette, Fernando; Sánchez, Morella; Rodríguez Arias, Eloy (Ciencia)
The role of Cu in the hydrodenitrogenation (HDN) of pyridine on molybdenum sulfide surface is studied with a CNDO method reparameterized for diatomic binding energies. A model system of a hydrogenated Mo2MeS8 cluster (Me = Cu or Mo) and a pyridine molecule were used to simulate the HDN process. Theoretical results show that the highest adsorption energy is found on the copper atom when this metal is located in a central position between two Mo atoms. Furthermore, the best adsorption mode occurs to the case in which the pyridine C2v axis is parallel to the Cu-S-Mo axis. Pyridine hydrogenation is explained by a notable interaction between hydrogen atoms adsorbed on Mo atoms neighboring the adsorption site and C and N atoms of the organic compound. Copper adsorption site presents: (a) A negative charge density due to electronic transference from lateral Mo atoms. (b) Weaker Me-S and Me-Mo bonds than in the case of pure MoS2, which makes difficult to substitute Mo by Cu. (c) The Mo-S bonds are stronger in Mo2CuS8, than in Mo3S8, which does not facilitate adjacent vacancy formation around the adsorption site and impedes the pyridine hydrogenation.